(untitled) (Bangladesh Journal of Medical Science, 2024)
The goal of modern dentistry is to treat cavitated or non-cavitated teeth through non-invasive remineralization to prevent further progression of caries and to improve the function of teeth. Many preventive interventions have been put forward as an alternative to conventional restorative procedures; silver diamine fluoride (SDF) is one amongst them. SDF can arrest progression of carious lesion at a concentration of 12% and 38% preventing further caries growth. The aim of this paper is to consider whether SDF is really a magic alternative in caries management or not. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 993-998